2020
DOI: 10.1093/biolinnean/blaa177
|View full text |Cite
|
Sign up to set email alerts
|

Only males care about their environment: sex-biased dispersal in the asp viper (Vipera aspis)

Abstract: Sex-biased dispersal is common among vertebrates and numerous studies have documented a tendency towards male-biased dispersal in mammals and female-biased dispersal in birds. A few studies have demonstrated that male-biased dispersal seems to be prevalent in reptiles. However, most of these studies considered only a single study site without taking into account possible local variability. We investigated sex-biased dispersal in Vipera aspis in four study sites in Switzerland using microsatellite markers and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
1
6
2
Order By: Relevance
“…mucrosquamatus snakes exhibit female‐biased dispersal. This result differs from previous studies on sex‐biased dispersal in snakes (e.g., Stegonotus cucullatus , Drymarchon couperi , Thermophis baileyi , Rhinoplocephalus nigrescens , Aipysurus laevis , Coronella austriaca , and Vipera aspis ) (Dubey et al, 2008 ; Folt et al, 2019 ; Hofmann et al, 2012 ; Keogh et al, 2007 ; Lukoschek et al, 2008 ; Pernetta et al, 2011 ; Zwahlen et al, 2021 ). However, most indices representing sex‐biased dispersal did not differ significantly, which may be the result of incomplete sampling.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…mucrosquamatus snakes exhibit female‐biased dispersal. This result differs from previous studies on sex‐biased dispersal in snakes (e.g., Stegonotus cucullatus , Drymarchon couperi , Thermophis baileyi , Rhinoplocephalus nigrescens , Aipysurus laevis , Coronella austriaca , and Vipera aspis ) (Dubey et al, 2008 ; Folt et al, 2019 ; Hofmann et al, 2012 ; Keogh et al, 2007 ; Lukoschek et al, 2008 ; Pernetta et al, 2011 ; Zwahlen et al, 2021 ). However, most indices representing sex‐biased dispersal did not differ significantly, which may be the result of incomplete sampling.…”
Section: Discussioncontrasting
confidence: 94%
“…Based on our total dataset, females had higher F is , H s , and vAIc values, but lower F st , r, and mAIc values than males (Tables 4 and 5), suggesting that P. mucrosquamatus snakes exhibit female-biased dispersal. This result differs from previous studies on sex-biased dispersal in snakes (e.g., Stegonotus cucullatus, Drymarchon couperi, Thermophis baileyi, Rhinoplocephalus nigrescens, Aipysurus laevis, Coronella austriaca, and Vipera aspis) (Dubey et al, 2008;Folt et al, 2019;Hofmann et al, 2012;Keogh et al, 2007;Lukoschek et al, 2008;Pernetta et al, 2011;Zwahlen et al, 2021).…”
Section: Sex-biased Dispersalcontrasting
confidence: 99%
“…There has been less generalization about potential causes and direction of sex‐biased dispersal in non‐avian reptiles despite a plethora of studies investigating and documenting its existence. All of the studies testing for sex‐biased dispersal found male‐biased dispersal (snakes: Dubey et al, 2008 ; Folt et al, 2019 ; Francois et al, 2021 ; Hofmann et al, 2012 ; Keogh et al, 2007 ; Rivera et al, 2006 ; Zhong et al, 2017 ; Zwahlen et al, 2021 ; lizards: Dubey & Shine, 2010 ; Johansson et al, 2008 ; Olsson & Shine, 2003 ; Stow et al, 2001 ; crocodiles: Tucker et al, 1998 ; turtles: Casale et al, 2002 ; Chaloupka & Limpus, 2002 ; FitzSimmons et al, 1997 ; Lee et al, 2007 ; Moore et al, 2020 ; Paquette et al, 2010 ; Sheridan et al, 2010 ) with the exception of one species of lizard (Chapple & Keogh, 2005 ). Our understanding of which sex is more likely to disperse during sex‐biased dispersal in birds and mammals can provide insight into the causation underlying the general pattern of male‐biased dispersal in non‐avian reptiles.…”
Section: Introductionmentioning
confidence: 99%
“…These situations can result in populations where the original mtDNA remains in place but occurs in a nuclear genetic background that has been massively swamped by the invading species (as recently proposed for Iberian hares by Seixas et al, 2018). Studies of sex‐biased dispersal in Viperidae are rare but Clark et al (2008, Crotalus horridus ), Zwahlen et al (2021, Vipera aspis ) and François et al (2021, V . berus ) reported male‐biased dispersal.…”
Section: Discussionmentioning
confidence: 99%